Study of The Influence of Gray Quality on Rice Quality in Every Milling Unit in Kabawo District, Muna Regency - Aswan ASWAN; Hermanto Hermanto; Sakir Sakir (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2022)
This study aimed to study the effect of grain quality on rice quality in each milling unit in Kabawo District, Muna Regency. The population in this study were all managers of rice mills, totaling two businesses. This research was conducted in Kabawo District, Muna Regency, Southeast Sulawesi. Sampling in this study used a descriptive analysis method by selecting a sample of 2 respondents. The results showed that the X-milling effort was quite high. Namely, X milling obtained a weight loss value of 3.6%, a Gilling yield of 66.56%, and the components of quality analysis were grain head rice, broken grain rice (28.1%), and groats grain rice (2.5%). While the milling effort Y is quite low. Namely, milling Y gets a weight loss value of 12.8%, yield milled, 61.24%, and the component of quality analysis is grain head rice, 68.6%, broken grain rice, 28.2 and groats rice, 2.5 %